Feeding Biology of Syrigma sibilatrix (Birds: Ardeidae) in a wetland of the Middle Parana River, Argentina (UNED Research Journal, 2017)
The diet of Syrigma sibilatrix (n=19) was studied in Carabajal Island (31°39´S, 60°42´W) from 1999 to 2003. The trophic spectrum was composed of 14 taxonomic units of animal taxa. Trophic diversity ranged between 0.23 and 2.15. Index of relative importance was of 10780 for insects, 1800 for arachnids and crustaceans, and 1750 for vertebrates. Most of the prey were represented by individuals included in the 0-20 mm (45%) and 21-40 mm (35%) size intervals. Trophic niche breadth was of 1.98 in spring, 2.34 in summer, 2.21 in autumn, and 1.99 in winter; standardized values were of 0.075 in spring, 0.10 in summer, 0.09 in autumn, and 0.076 in winter. Feeding efficiency was 96.01% in spring, 98.3% in summer, 89.9% in autumn and 92.34% in winter. No evidence was found of food selectivity. The highest percentage of site fidelity (69%) corresponded to the grassland environment. In conclusion, the results indicated that in the floodplain of the Middle Parana River, S. sibilatrix has a diet based primarily on insects obtained mainly in the environmental unit of grasslands.
Keywords: Feeding ecology; waterbirds; floodplain